Evidence for Forward Spin and Reverse Spin Radio Photons - Marvin Motsenbocker (International Journal of Radio Frequency Innovations, 2023)
We generated alternate spin radio frequency photons by accelerating metallic valence electrons in a wire with half portions of a sine wave. To avoid standing waves from sinusoidal movement, a non-resonating transmitter was built with a non-resonating antenna. An oscilloscope at a second non-resonant receiving antenna 3 wavelengths away from the transmitter detected positive going 180-degree voltage pulses. Reversing the direction of electron excitation in the transmitter antenna caused negative going 180-degree electric pulses in the receiver. The results confirm that photons produced by radio transmissions are of two types, forward +1 spin and reverse -1 spin. In the radio wave context, we may consider a zero spin 2-photon pair as a naturally occurring unit that forms waves. This research points the way to a much higher speed communication format based on photon pulses and not wave trains.
Keywords: Antenna; MOSFET; Oscilloscope; Reverse Spin; photons